STUDI KELAYAKAN BISNIS UMKM ENDEK PADA TENUN IKAT SRI WIDHI DI KABUPATEN KLUNGKUNG, BALI - Ni wayan Ari Sudiartini; Ni Luh Indiani; I Putu Agus Adiyasa (Widyadari : Jurnal Pendidikan, 2022)
This research was conducted with the aim of determining the business feasibility of Sri Widhi's Endek Tenun Ikat UMKM in terms of non-financial and financial aspects. To analyze non-financial aspects consisting of market aspects, technical aspects, as well as management and HR aspects, qualitative descriptive methods were used while financial aspects were analyzed using quantitative descriptive methods with the help of Microsoft Excel program. The results of the analysis obtained from non-financial aspects, Sri Widhi's Endek Ikat Weaving UMKM business is still categorized as still feasible to run but there are several things that need to be evaluated and improved in marketing strategies related to promotional activities still relying on suppliers and word of mouth strategies so that market share absorption is still limited, and still using ATBM (Non-Machine Weaving Equipment). Meanwhile, the results of the analysis of the financial aspect show that the UMKM Endek Weaving Ikat Sri Widhi business is feasible to run. This can be seen from the NPV (Net Present Value) obtained > 0 and has a positive value of Rp. 2,030,577,166. The resulting IRR (Internal Rate Of Return) value> commercial bank interest rate is 17.47%. The resulting payback period is < from the investment age, which is 3.2 years. Profability Index (PI) obtained > 1, which is 1.18.